Microwave-assisted synthetic method of novel Bi2O3 nanostructure and its application as a high-performance nano-catalyst in preparing benzylidene barbituric acid derivatives - Yahyazadehfar, Mahdieh; Sheikhhosseini, Enayatollah; Ahmadi, Sayed Ali; Ghazanfari, Dadkhoda (Frontiers in Chemistry, 2022)
In this study, controllable and optimal microwave irradiation has been used to synthesize the novel nanostructures of Bi2O3 under environmental conditions. The final products had a thermal stability of 210 °C, an average particle size distribution of 85 nm, and surface area of 783 m2/g. The high thermodynamic stability of Bi2O3 nanostructures were confirmed by TG and DSC analyses. The nanostructure nature of compounds, most importantly, the use of effective, cost effective and rapid synthesis route of microwave have created significant physiochemical properties in the Bi2O3 products. These unexpected properties have made the possibility of potentials application of these products in various fields, especially in nano-catalyst applications. It is well-documented that, as Lewis acid, bismuth nano-catalyst exhibits a great catalytic activity for the green synthesis of some bio-active barbituric acid derivatives using precursors with electron-donating or –withdrawing nature in high yields (80-98%). After incorporating this catalyst into the aqueous media, all the reactions were completed within 2-3 min at room temperature. The main advantages of this method are practical facility, the availability of starting materials, and low costs besides the catalyst reusability. Additionally, the catalyst synthesis process may be carried in the aqueous media during a short period with medium to high yields. The obtained results have opened a new window for development of a novel nano-catalyst with practical application.